2017
DOI: 10.1590/1677-5449.002117
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de tromboembolismo pulmonar incidental em pacientes oncológicos: análise retrospectiva em grande centro

Abstract: Background: Increased use of routine imaging exams has led to higher rates of incidental diagnosis of pulmonary thromboembolism (PTE), especially for management of disease in cancer patients, among whom it is an important factor in associated morbidity and mortality. Objective: To identify cases of incidental PTE in cancer patients examined with computed tomography (CT) of the thorax, correlating clinical features and associated risk factors. Methods: This is a retrospective study of all episodes of PTE diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
0
4
0
9
Order By: Relevance
“…A Figura 1 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) mostra os resultados dos artigos científicos utilizados nesta pesquisa, provenientes da busca bibliográfica com os descritores específicos e gerais, realizada na Biblioteca Virtual em Saúde.…”
Section: Resultsunclassified
“…A Figura 1 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) mostra os resultados dos artigos científicos utilizados nesta pesquisa, provenientes da busca bibliográfica com os descritores específicos e gerais, realizada na Biblioteca Virtual em Saúde.…”
Section: Resultsunclassified
“…The comorbidities associated most strongly with TEP diagnosis were history of TEP, Deep vein thrombosis -TVP, the use of systemic anticoagulants, pulmonary diseases, and benign prostate hyperplasia BPH. 4,6,12 The most prevalent types of cancer in Group 1 were lung, breast, colorectal, and prostate. Lung, pancreas, and brain cancers were significantly associated with a positive TEP diagnosis (p=0.021, p=0.003, and p=0.043, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…8,11 The cancro Lung, pancreas and brain were also described in a Brazilian retrospective study and an American cohort study, conducted from 2013 to 2017, which analysed the prevalence of incidental TEP in cancer patients showing a greater association of these types of cancer with thromboembolic event diagnosis and TEP. 12,15 Some studies have shown that patients with metastatic cancer had a greater association with the diagnosis of positive TEP. 1,6,12 However, we did not observe any significant association between metastatic cancer and TEP in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) O risco de TEP aumenta com a idade, assim como ocorre com comorbidades frequentemente associadas ao envelhecimento, como as doenças cardiovasculares, pulmonares crônicas e oncológicas. (4,5) Esse perfil de pacientes mais complexos contribui para internações mais prolongadas, com custos mais elevados e maiores riscos de morbidade e mortalidade relacionados aos eventos tromboembólicos. (4) Diante da maior expectativa de vida da população nas últimas décadas, com elevação do índice de envelhecimento no Brasil de 268% de 1970 a 2010, principalmente nas regiões Sul e Sudeste, (6) observou-se um aumento do número de internações hospitalares por TEP: a média de internações em 2008 e 2019, respectivamente, foi de 2,57/100.000 habitantes e 4,44/100.000 habitantes.…”
unclassified